Vitamin D levels and depression in type 2 diabetes mellitus patients: a cross-sectional study - Putranto, Rudi; Adhiatma, Kresna; Tarigan, Tri Juli Edi; Rumende, Cleopas Martin; Shatri, Hamzah; Rengganis, Iris; Nugroho, Pringgodigdo; Rinaldi, Ikhwan (Medical Journal of Indonesia, 2023)
BACKGROUND The prevalence of type 2 diabetes mellitus (T2DM) is increasing and commonly accompanied by comorbidities, such as depression. Vitamin D levels have been associated with T2DM and depression although the mechanism is uncertain. This study aimed to compare vitamin D levels between patients with T2DM with and without depression in the Indonesian community, where such research is rare. METHODS This cross-sectional study was conducted at Cipto Mangunkusumo Hospital. The participants who met the inclusion criteria on an outpatient basis were screened for depression using the Beck Depression Inventory-II (BDI-II) questionnaire and then divided into 2 groups: patients with T2DM with (BDI-II ≥14) and without (BDI-II <14) depression. Both groups were examined for vitamin D levels using the ELISA method, and an analysis of the mean difference between both groups was performed. RESULTS Of 60 patients, 23 (38%) experienced depression. The median vitamin D levels were 21.8 ng/ml (IQR 14.9–26.6) in the depression group and 26.5 ng/ml (IQR 23.96–34.08) in the non-depression group (p = 0.001). After performing multivariate analysis with confounding variables, the adjusted OR of variables (sex, sun exposure score, and body mass index) was 1.123 (95% CI: 1.003–1.259; p = 0.045). CONCLUSIONS Vitamin D levels were significantly lower in patients with T2DM with depression. Future studies should be carried out to determine the benefits of vitamin D supplementation in patients with T2DM with depression and their pathophysiology.